2012
DOI: 10.7314/apjcp.2012.13.11.5593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Group Therapy on Psychological Symptoms and Quality of Life in Turkish Patients with Breast Cancer

Abstract: Purpose: The aim of this study was to evaluate the effects of the group therapy on psychological symptoms and quality of life of patients with early stage breast cancer. Methods: This study was performed on 16 breast cancer patients who completed treatments. The total group therapy program involved a weekly session of 2-3 hours, for 16 weeks. The group therapy sessions were given to women in the oncology department by a clinical psychologist and also given training sections by the different professional teams.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 38 publications
2
43
0
2
Order By: Relevance
“…A pilot study from the same country showed that group therapy leads to significant reduction in depression, anxiety and distress for patients with breast cancer (Yavuzsen et al, 2012). In contrast, only 8.8% of study participants received psychological counseling after diagnosis and only 2.7% participants in psychosocial support program.…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study from the same country showed that group therapy leads to significant reduction in depression, anxiety and distress for patients with breast cancer (Yavuzsen et al, 2012). In contrast, only 8.8% of study participants received psychological counseling after diagnosis and only 2.7% participants in psychosocial support program.…”
Section: Discussionmentioning
confidence: 99%
“…DOI:http://dx.doi.org/10.7314/APJCP.2015.16.2.641 Post-traumatic Stress Disorder and Post-traumatic Growth in Breast Cancer Patients -a Systematic Review iii) Both PTSD and PTG in BC survivors (Tjemsland et al, 1998;Cordova et al, 2001;Jones, 2001;Sumalla et al, 2009;Ho et al, 2011;Chan et al, 2011;Koutrouli et al, 2012;Liu et al, 2014). iv) PTSD and psychological distress and diagnostic challenges in the same patient population (Gurevich et al, 2002;Tedeschi and Calhoun, 2004;Bellizzi et al, 2010;Rustad et al, 2012;Yavuzsen et al, 2012;Abu-Helalah et al, 2014;Chang et al, 2014;Rizalar et al, 2014) and v) Treatment approaches (Andrykowski et al, 2000;Levine et al, 2005;Knobf, 2007;Bellizzi et al, 2010;Assi et al, 2013;Liu et al, 2014) Discussion PTSD is a psychiatric condition that occurs as a result of exposure to a traumatic event, defined as a threat of death or serious injury (Kangas et al, 2002). This in turn evokes intense fear, helplessness, or horror (DSM-IV, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…from the psychological point of view (Anderson and Johnson, 1994;Stanton and Reed, 2003;Yavuzsen et al, 2012]. Due to the significance of the breast for women, anxiety concerns about the possible loss, as well as the actual loss of the breast, can damage feelings of sexuality, motherhood, body image and attractiveness.…”
Section: Introductionmentioning
confidence: 99%